2001
DOI: 10.1007/s004640000330
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative thermal regulation in patients undergoing laparoscopic vs open surgical procedures

Abstract: This study demonstrates that patients who undergo laparoscopic and open procedures of similar duration under endotracheal general anesthesia have similar profiles in terms of perioperative hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
2
19
0
3
Order By: Relevance
“…In addition, like open abdominal surgeries, the patient is anesthetized and exposed to irrigation fluids within the peritoneal cavity. Our results mimicked those of many other studies that showed no significant difference in hypothermia between patients having laparoscopic versus open surgeries 32,45,46. …”
supporting
confidence: 93%
“…In addition, like open abdominal surgeries, the patient is anesthetized and exposed to irrigation fluids within the peritoneal cavity. Our results mimicked those of many other studies that showed no significant difference in hypothermia between patients having laparoscopic versus open surgeries 32,45,46. …”
supporting
confidence: 93%
“…Rectal temperature change due to laparoscopy is controversial in humans (Luck et al 1999, Berber et al 2001, Cohen et al 2003 and little information in animals is available in this subject. Our results suggest that the pneumoperitoneum in not an important cause of hypothermia, and the lower rectal temperatures found in laparoscopy is related to longer surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…However, incidences of shivering, due to heat loss from insufflation gas and irrigation fluid and heat redistribution after anesthesia, have been reported to be similar for laparoscopic and open procedures [5][6][7]. Furthermore, although the most commonly used drugs, meperidine and clonidine, have potent anti-shivering effects [8], these may cause hemodynamic and respiratory suppression due to their sympatholytic actions.…”
Section: Introductionmentioning
confidence: 99%